Developing multimedia learning on concept Arthropoda to increase students self-regulation and motivation - Wahyu Maulana Endris; Suhartini Suhartini (Jurnal Inovasi Pendidikan IPA, 2022)
This study aims to: (1) produce learning multimedia, (2) determine the feasibility of learning multimedia, and (3) determine the effectiveness of multimedia learning in increasing independence, motivation, and learning outcomes of biology subjects. This development research uses the ADDIE model, namely the analysis, design, development, implementation, and evaluation stages. Data collection techniques in the study used observation sheets, interview guides, learning style questionnaires, cognitive tests, learning independence questionnaires, learning motivation questionnaires, and experience questionnaires using media. Quantitative data on learning outcomes were obtained and then analyzed using paired t-tests. The results showed that: (1) the product was learning multimedia valid and reliable, (2) multimedia learning on Arthropod material is suitable for use in biology learning; and (3) learning using multimedia is effective in increasing independence, motivation, and learning outcomes of biology students.